Effect of Orange-Fleshed Sweet Potato Purée and Wheat Flour Blends on β-Carotene, Selected Physicochemical and Microbiological Properties of Bread - Malavi, D.N.; Mbogo, D.; Moyo, M.; Mwaura, L.; Low, Jan W.; Muzhingi, T. (MDPI, 2022)
Partial substitution of wheat flour with orange-fleshed sweet potato (OFSP) purée in bread can increase vitamin A intake among consumers. The study investigated the influence of wheat flour substitution with 20–50% of OFSP purée on proximate composition, color, β-carotene, water activity, and microbial keeping quality. The moisture content, crude protein, crude fat, total ash, crude fiber, and carbohydrate in bread ranged from 28.6–32.7%, 9.9–10.6%, 5.0–5.5%, 1.9–3.2%, 1.4–1.8%, and 79.1–80.9%, respectively. β-carotene, total ash, and crude fiber contents in bread, and Hunter color values a*, b*, chroma, and ∆E significantly increased with the addition of OFSP purée. Total viable counts (TVC), yeast, and molds in bread ranged from 2.82–3.64 log10 cfu/g and 1.48–2.16 log10 cfu/g, respectively, on the last day of storage. Water activity, TVC, and fungal counts were low in sweet potato composite bread as compared to white bread. Total β-carotene in OFSP bread ranged from 1.9–5.4 mg/100 g (on dry weight). One hundred grams of bread portion enriched with 40% and 50% OFSP purée provides more than 50% of vitamin A dietary requirements to children aged 4–8 years. Incorporation of up to 50% OFSP purée in wheat flour produces a relatively shelf-stable, nutritious, and health-promoting functional bread.